Itaconic acid production by Aspergillus terreus from glucose up to pilot scale and from corn stover and wheat straw hydrolysates using new manganese tolerant medium. (August 2022) - Saha, Badal C.; Kennedy, Gregory J.; Bowman, Michael J.; Qureshi, Nasib; Nichols, Nancy N.
Abstract: Itaconic acid (IA), is a versatile platform chemical that is produced by Aspergillus terreus using glucose as carbon source. Lignocellulosic biomass can be used as a low cost source of sugars for IA production. However, A. terreus does not produce IA even after 100 fold dilution from enzymatically hydrolyzed wheat straw pretreated with dilute acid. In addition to organic inhibitors, Mn 2+ strongly inhibits IA production. Mn 2+ was present in the hydrolysate at a level 230 times over the inhibitory limit (50 ppb). Recently, PO4 3− limitation was shown to decrease the inhibitory effect of Mn 2+ on IA production and a medium was formulated in which A. terreus produced IA very efficiently in the presence of Mn 2+ up to 100 ppm. Here, the effectiveness of this medium was demonstrated at pilot scale using a stainless steel bioreactor and glucose as the substrate. The productions of IA from corn stover cellulosic hydrolysate in a biorefinery concept and mitigated wheat straw hydrolysate using the Mn 2+ tolerant medium were also demonstrated at laboratory scale. The fungal strain produced 74% IA from cellulosic hydrolysate and 98% IA from wheat straw hydrolysate in comparison with respective mock sugar solution. This is the first report on using Mn 2+ tolerant medium to achieve IA production by A. terreus on hydrolysates . Highlights: Itaconic acid production in Mn tolerant medium was evaluated in different bioreactors. Itaconic acid production using Mn tolerant medium was demonstrated at pilot scale. The fungal strain produced itaconic acid well from corn stover cellulosic hydrolysate. Excellent itaconic acid yield was achieved from mitigated wheat straw hydrolysate. This is first report on evaluation of Mn tolerant medium for itaconic acid production.